Tocilizumab in the treatment of adult rheumatoid arthritis. (2nd March 2018) - Sanmartí, Raimon; Ruiz-Esquide, Virginia; Bastida, Carla; Soy, Dolor
Rheumatoid arthritis (RA) is the most prevalent immune-mediated chronic rheumatic disease and is associated with joint destruction and disability. Therapeutic strategies, including biological disease-modifying antirheumatic drugs (bDMARDs) have improved the prognosis and quality of life of RA patients. Tocilizumab (TCZ) is a humanized monoclonal antibody against IL-6 receptor licensed in 2009 that has demonstrated clinical efficacy in various adult RA populations. RA management guidelines and recommendations consider TCZ as one of the bDMARDS indicated after methotrexate or other conventional synthetic DMARDs and/or TNF inhibitors failure in adult RA. Of particular interest is the demonstration of its effectiveness in monotherapy in comparison with other bDMARDs. Recent observational studies have shown good results for the safety profile of TCZ with no new alert signals.